Association of Blood Pressure Variability and Intima-Media Thickness With White Matter Hyperintensities in Hypertensive Patients - Chen, Xin; Zhu, Yingqian; Geng, Shasha; Li, Qingqing; Jiang, Hua (Frontiers in Aging Neuroscience, 2019)
Background and Purpose: Ambulatory blood pressure variability (ABPV), ambulatory blood pressure (ABP) and carotid intima-media thickness (IMT) are closely associated with white matter hyperintensities (WMH), few studies focused on establishing effective models based on ABP, ABPV and IMT to predict the WMH burden, we aimed to evaluate the value of predictive model based on metrics of ABP, ABPV and IMT which were independently associated with the WMH burden. Methods: We retrospectively enrolled 140 hypertensive inpatients for physical examinations in Shanghai East Hospital, Tongji University School of Medicine between February, 2018 to January, 2019. The basic clinical information of all subjects were recorded and we also collected the metrics of ABP, ABPV and IMT. Patients with Fazekas scale grade ≥2 were classified into heavy burden of WMH group. Then we analyzed the association between all characteristics and the WMH burden. Multivariate analysis was performed to assess whether metrics of ABP, ABPV and IMT were independently associated with WMH and we used receiver operating characteristic (ROC) to evaluate the value of predictive model based on metrics of ABP, ABPV and IMT. Results: Higher WMH grade was associated with increasing age, diabetes mellitus, higher TC, higher LDL, higher IMT, higher 24-hSBP, higher daytime SBP, higher nocturnal SBP, 24-h and daytime SD of SBP, and 24-h SBP weight SD; 24-h SBP, 24-h SBP-SD and IMT were independently related to the burden of WMH even after adjusting for the clinical variables; In addition, we also established a model which has a higher predictive capacity using 24-h SBP, 24-h SBP-SD and IMT in ROC analysis to assess the WMH burden in hypertensive patients. Conclusions: Higher 24-h SBP, higher 24-h SBP-SD, and larger IMT were independently associated with greater burden of WMH among elderly Asian primary hypertension patients, establishing a model based on these factors might provide a new approach for enhancing the accuracy of diagnosis of WMH using metrics in 24-h ABPM and carotid ultrasound.